Obtención de cerveza artesanal ale usando sachapapa (Dioscórea trífida L.) como sucedáneo de la malta de cebada y cocona (Solanum sessiliflorum D.), Iquitos 2022 - Pereira Ramirez, Max Ney (2023)
The main objective of this research work was to obtain Ale craft beer, using sachapapa as a substitute for barley malt and cocona extract. For this reason, three formulations were made to elaborate the beers modifying the proportions (P1 90% barley-10% sachapapa, P2 80% barley-20% sachapapa and P3 70% barley-30% sachapapa), to all the proportions it was added 30% cocona extract. The products obtained were subjected to a determination of the organoleptic parameters by a certified jury, obtaining the following results: the three formulations P1, P2 and P3, were within the range of 21 to 29 points, defining them as good beers. Likewise, a hedonic test was carried out to compare the attributes (smell, color, taste, appearance and acceptability), through a sensory analysis applied to a population of thirty untrained people. The results obtained from the survey showed a p>0.05 for all the medians of the attributes evaluated, therefore, there was no statistical significance between the proportions P1, P2 and P3. However, the data, having been graphically compared, showed that the beer made with the proportion P1 (90% barley and 10% sachapapa) was the best evaluated by those surveyed. The physicochemical and microbiological analysis carried out on the P1 formulation indicated that it complies with the parameters established by the Peruvian Technical Standard 213.014 2022. Finally, it was concluded that sachapapa starch can be used as a substitute for barley malt accompanied by the extract of cocona in the brewing of Blonde Ale style craft beer.